Efektifitas dan Efisiensi Penggunaan Sistem Informasi Komputerisasi Akuntansi Pada Perumda Tirta Manuntung Balikpapan - YUSVANZA BRIYAN SAPUTRA (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to determine the impact of the effectiveness and efficiency of using computerized accounting information systems. This research was conducted at Perumda Tirta Manuntung Balikpapan. The method used is qualitative and the technique used is interviewing. The test results of this study, namely the Use of Computerized Information Systems accounting, have an effective impact by looking at time, data input, productivity, supervision and work evaluation and the use of Computerized Information Systems Accounting has an efficiency impact by seeing that the number of data output results produced is greater than the number of data input results. The impact of this effectiveness and efficiency is due to the various features available in the Computerized Accounting Information System that make it easier for users to input journals and make financial reports.